Surgical treatment of merycism in an adult. - Carriquiry, Luis A; Lyonnet, Alberto J; Peyroulou, Alfredo; Pradines, Jorge C (Cirugía del Uruguay, 1978)
The authors present a clinical observation of m,i!rycism in au adult who was treated by means of _a Nissen type fundoplication. With regard to this case, the authors draw attention to it? rarity, to the fact that its real etiolo·gy is unknown, to its differences from vomiting and from rumination in animals and to its location within the syndrome of gastoesophagic reflux. They aiso pointed out that when this disorder becomes a inconvenient to life in society, an anti-reflux o·peration may be indicated.